Development of Contextual-Based Chemistry Module on Hydrocarbon Compound Materials - Tiurlina Siregar; Semuel Franklyn Yawan; Freddy Tua Musa Panggabean (Jurnal Inovasi Pembelajaran Kimia (Journal of Innovation in Chemistry Education), 2024)
The lack of modules as teaching materials is an obstacle in learning chemistry, especially hydrokron compound material. Therefore, this study aims to develop and validate the feasibility of chemistry e-modules on contextual-based hydrocarbon compound materials and to assess how students and teachers respond to the products developed. Research and development (R&D) method is the method used and ADDIE is the development model applied as methodology. Hydrocarbon compounds as the subject of this study. The modules developed are very feasible to be applied in chemistry learning, according to the results of the data analyzed.The average assessment of lecturer validators 87% is very feasible and the teacher's response is 93% very good, the response of students 92% is very good